Ameliorative Effect of Ethanolic Extract of Peperomia pellucida on Anxiety in Pentylenetetrazol-Induced Epileptic Seizure in Mice - Enene, Esu Ukpai; Ango, Ashiya; Ajah, Obia Ukwula; Ating, Ante Iniobong; Ukoh, Imoh Emmanuel (Darul Yasin Al Sys, 2025)
Although Peperomia pellucida has been traditionally used to manage central nervous system disorders, its anxiolytic properties remain insufficiently characterized. This study aimed to evaluate the anti-anxiety potential of ethanolic extract of Peperomia pellucida in a pentylenetetrazol (PTZ)-induced epileptic mouse model. Forty male Swiss albino mice (21–35 g) were randomly divided into four groups (n = 10 per group): Group A (control), Group B (PTZ 35 mg/kg, intraperitoneally), Group C (PTZ 35 mg/kg + P. pellucida 2 mg/kg, orally), and Group D (PTZ 35 mg/kg + Diazepam 0.001 mL/kg, orally). Epilepsy was induced via PTZ, confirmed by characteristic jerky movements progressing to generalized convulsions. Treatment was administered for 14 days prior to behavioral assessments. Anxiolytic activity was evaluated using the elevated plus maze and light/dark transition test. Behavioral data were analyzed using IBM SPSS Statistics version 20, with significance set at p < 0.001. Mice treated with P. pellucida exhibited significant reductions in anxiety-like behavior compared to the PTZ-only group, demonstrating increased time spent in the open arms of the elevated plus maze and in the light compartment of the light/dark box. These effects were comparable to those observed in the Diazepam-treated group. The findings suggest that ethanolic extract of Peperomia pellucida possesses notable anti-anxiety activity in PTZ-induced epileptic mice, supporting its potential as a complementary therapeutic agent for anxiety-related conditions.